Initiations in the Burmese Ritual Landscape - Bénédicte Brac de la Perrière (Journal of Ethnology and Folkloristics)
In Buddhist Burma, a variety of ritual has been found pertaining to quite differentiated aspects of religion. This rich ritual landscape remains under-examined due partly to the Buddhist-studies bias of most of the scholars looking at religion in Burma. In this paper, I develop comparative analysis of a class of ritual, namely that of initiation, in three components of Burmese religion: Buddhist monasticism, Buddhist esotericism, and spirit worship. At least from the present analytic perspective, the three components considered could be taken as encompassing the entire Buddhist religious sphere in Burma. Looking at initiation rituals in these three ‘paths’ is a means of understanding how they frame contrasting kinds of differently valued religious practice, and of showing that, although not often discussed, rituals do matter in Burma because they help distinguish categories of action according to their relative religiosity. By doing so, I aim to give a sense of the real diversity of the Burmese ritual landscape, which until recently was rarely taken into account, and to contribute to the on-going debate in the field of Buddhist studies on what could be encapsulated as the question of Buddhism and spirit cults in Southeast Asian Theravada.